Steam Education Route in Vietnam: Framework and Students’ Perspective - Huu Hau, Nguyen; Trung Tinh, Tran; Thuy Van, Nguyen (International Journal of Psychosocial Rehabilitation, 2020)
In terms of the technological development that has significantly proposed and influenced STEAM education. We elaborate to self-develop a STEAM framework and explore the perspective student’s effectiveness for learning and developing consequences. Herewith is an art education project that precisely considers the learning of the Vietnamese traditional instrument (called T’rung) in the high school curriculum of the 11th grade. A self-process of 7 steps with 4 experts, 7 teachers, and 1 principal was contributed to generate a framework that probably confirms the procedure of STEAM excellency. On top, a qualitative method with a semi-structured evaluation of 16 students was carried out to explore their perspective usages of the STEAM education implemented. Collected data was measured and analyzed by NVIVO 12 software in theme development. The results reveal a STEAM framework with three stages of "problem-solving activity via STEAM skills and integrated learning capabilities," "teaching process to create knowledge," and "self-seeking solutions in STEAM." These obtained frameworks, together with assessment criteria of students’ outcomes such as creativity, innovation, prototype, explanation, research, information, fluency, presentation, and visual appeal, were acquired. This may have a perspective impact to improve the quality of STEAM education in the Vietnamese circumstance.